Ionopiezoelectric hydrogel for urethral sponge defect repair and preparation method thereof
Patent Information
- Application Number
- CN202611519520.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0011]现有技术的离子压电水凝胶虽具有一定的力电转换能力,但仍难以满足尿道海绵体修复的特殊需求,主要原因如下:
[0036](1)本发明以细菌纤维素纳米纤维网络为结构网络构建离子压电水凝胶,可在超声刺激下产生离子压电电信号,无需外接电源实现无线生物电刺激,解决现有修复材料缺乏主动生物电刺激能力、难以模拟天然组织生物电微环境的问题。
Smart Images

Figure CN122998058A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials and tissue repair technology, and relates to an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum and its preparation method. Background Technology
[0002] Injury and defects of the corpus spongiosum are challenging issues in urinary system tissue repair, often caused by factors such as trauma, iatrogenic injury, and congenital malformations. The corpus spongiosum not only maintains the structural integrity of the urethra but also plays a crucial role in regulating local blood flow, providing tissue support, and transmitting sensation. Therefore, its repair requires not only tissue filling but also restoration of vascularization, smooth muscle reconstruction, and tissue biomechanical function.
[0003] Currently, clinical repair primarily utilizes autologous tissue transplantation and bio-scaffold materials. Autologous tissue transplantation faces challenges such as donor site damage, limited tissue availability, and postoperative scarring. While decellularized matrix materials possess some biocompatibility, their mechanical properties and tissue-inducing capabilities are limited. Synthetic polymers like polylactic acid (PLA) and polyglycolic acid (PEG) suffer from degradation, acidification, and insufficient tissue compatibility. Although conventional hydrogel materials exhibit good flexibility and biocompatibility, they generally lack active bioelectric stimulation capabilities, making it difficult to effectively simulate the electrical microenvironment of natural tissues. Bacterial cellulose, due to its nanofiber network structure, high water content, good biocompatibility, and tunable mechanical properties, has attracted widespread attention in the field of tissue engineering scaffolds. However, research on the ionic piezoelectric response of bacterial cellulose under humid conditions has not yet been reported, and its ion migration behavior, piezoelectric output directionality, and structural regulation mechanisms remain unclear.
[0004] Recent studies have revealed the crucial role of bioelectric signals in angiogenesis, neural repair, and cellular behavior regulation, leading to widespread interest in piezoelectric biomaterials capable of converting mechanical stimulation into electrical signals. However, traditional inorganic piezoelectric materials suffer from insufficient flexibility and poor biocompatibility, while organic piezoelectric polymers generally exhibit strong hydrophobicity and insufficient biointegration. Furthermore, traditional piezoelectric materials primarily rely on electronic polarization mechanisms, making their piezoelectric properties susceptible to attenuation in moist physiological environments, thus hindering their suitability for repairing urethral tissues in complex ionic environments. Ultrasonic stimulation, with its non-invasive nature, strong tissue penetration, and remote controllability, is suitable for in-situ activation of implanted tissue-engineered materials.
[0005] Ion piezoelectric materials achieve the conversion between mechanical stimulation and electrical signals through ion migration regulated by a fixed charge. They possess characteristics such as softness, good biocompatibility, and suitability for humid environments, showing promising application prospects in tissue engineering. In recent years, studies have proposed constructing ion piezoelectric hydrogels using ion migration mechanisms to achieve the conversion between mechanical stimulation and electrical signals in humid environments.
[0006] For example, CN120586153B discloses a method for preparing an ionic piezoelectric hydrogel for the treatment of peripheral nerve injury, comprising the following steps: mixing and reacting a polyvinyl alcohol solution and a phytic acid solution, followed by freeze-thaw reaction to obtain the ionic piezoelectric hydrogel. In this invention, the phosphate groups of phytic acid and the hydroxyl groups of polyvinyl alcohol exhibit hydrogen bonding, which improves the mechanical properties of the hydrogel; the phosphate groups of phytic acid also have electrostatic interactions with sodium ions, restricting the movement of sodium ions and resulting in a significant difference in the diffusion coefficients of sodium and chloride ions, thereby greatly enhancing the piezoelectric output of the hydrogel.
[0007] For example, patent application CN120248226A provides a PAM ion piezoelectric hydrogel, its preparation method, and its application, including: preparing a hydrogel solution: adding AM and PAM to deionized water and stirring to mix and dissolve to obtain a precursor solution; slowly adding hydrochloric acid to the precursor solution; then adding sodium gluconate / sodium chloride and stirring at 60°C; adding MBAA and a UV photoinitiator at mass ratios of 0.01 and 0.016 with the added AM, respectively, and mixing to obtain an uncured hydrogel solution; synthesizing a PAM ion piezoelectric hydrogel with added bubbles: cooling the uncured hydrogel solution and stirring under UV light; adding sodium bicarbonate powder and stirring; after stirring, pouring the mixed solution into a mold and continuing to place it under UV light for irradiation to form a PAM ion piezoelectric hydrogel with bubbles.
[0008] Currently, ion-piezoelectric hydrogels are mainly used in the repair of skin, nerves, or soft tissues. The corpus spongiosum is a highly specialized spongy tissue that combines structural support, blood flow regulation, and physiological function transmission. Its repair is significantly more challenging than that of ordinary soft tissues, primarily due to the following unique characteristics: First, the corpus spongiosum is in a complex dynamic mechanical environment for a long time. Its tissues need to withstand the impact of urine flow, the periodic contraction and relaxation during urination, and local tissue deformation. Therefore, the repair material not only needs to have good flexibility and tissue compatibility, but also needs to maintain long-term stable mechanical properties and structural integrity in a wet environment. Otherwise, it is prone to collapse, scar contraction, or restenosis.
[0009] Secondly, the corpus spongiosum is a highly vascularized tissue, rich in sinusoidal structures, smooth muscle bundles, and microvascular networks. Its function depends on blood perfusion and the coordinated regulation of smooth muscle. Therefore, corpus spongiosum repair requires not only tissue filling but also the promotion of angiogenesis, smooth muscle reconstruction, and orderly tissue regeneration to restore normal tissue function, rather than forming simple fibrous scars.
[0010] Finally, the corpus spongiosum is in a physiological environment with high water content and high ion concentration for a long time. The natural tissue contains a dynamic bioelectric microenvironment formed by ion migration, transmembrane potential, and fixed charge. This microenvironment plays an important role in angiogenesis, cell migration, and tissue regeneration. Therefore, an ideal repair material not only needs to have good mechanical adaptability, but also should be able to provide stable, biomimetic electrical stimulation signals in a moist ion environment.
[0011] While existing ion-piezoelectric hydrogels possess a certain degree of electromechanical conversion capability, they still fall short of meeting the specific needs of urethral sponge repair. The main reasons are as follows: (1) Existing ion piezoelectric hydrogels mostly adopt disordered polymer network structures, with random ion migration paths inside. The ion migration directionality formed under mechanical stimulation is weak, which easily leads to low charge separation efficiency and unstable piezoelectric output, making it difficult to form a continuous and effective directional electrical stimulation signal.
[0012] (2) Most existing ion-piezoelectric hydrogels are not designed for the long-axial structural characteristics of the corpus spongiosum tissue. The corpus spongiosum is a tubular tissue with obvious directionality, and its blood vessels and smooth muscle are arranged axially. Therefore, it is more necessary to induce orderly tissue regeneration by in-plane electrical stimulation (d31 mode output) along the tissue direction. However, existing materials generally exhibit weak anisotropic ion-piezoelectric properties, making it difficult to form effective directional electrical stimulation.
[0013] (3) Existing ion piezoelectric hydrogels are mostly constructed based on homogeneous polymer systems such as PAAM, PVA, PEG, and sodium alginate. They lack natural layered nanofiber structures, making it difficult to form continuous low-resistance ion migration channels and thus failing to effectively improve ion migration efficiency and piezoelectric performance.
[0014] Therefore, it is necessary to propose an ion-piezoelectric hydrogel for the repair of defects in the corpus spongiosum and its preparation method. Summary of the Invention
[0015] The purpose of this invention is to address the problems existing in the prior art and to provide an ion-piezoelectric hydrogel for the repair of defects in the corpus spongiosum and its preparation method.
[0016] To achieve the above objectives, the technical solution adopted by the present invention is as follows: An ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum includes a structural network and a salt solution distributed in the structural network. The structural network is a bacterial cellulose nanofiber network obtained by direct culture of bacterial strains. Ionic piezoelectric hydrogels are used in ultrasonic applications with an intensity of 0.3~2 W / cm. 2Under ultrasonic stimulation, it can generate an ion piezoelectric output voltage of 379.6~1944.7mV (ion piezoelectric output voltage = d31 mode ion piezoelectric output voltage + d33 mode ion piezoelectric output voltage), and the d31 mode ion piezoelectric output voltage is higher than the d33 mode ion piezoelectric output voltage; After implantation, the ion-piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the proportion of mature blood vessel area reaches 6.4% to 9.8%, and the proportion of smooth muscle area reaches 24.8% to 38%, which can reach the level of normal urethral sponge.
[0017] This invention discovers that bacterial cellulose nanofiber networks obtained directly from bacterial strains can generate an ionic piezoelectric response after ultrasonic stimulation in a moist ionic environment. This is because even without chemical modification, the bacterial cellulose nanofiber network possesses a certain negative surface potential (Zeta potential value of -16.6mV) in an aqueous environment. Upon ultrasonic stimulation, the negative surface potential of this natural layered nanofiber network can induce asymmetric migration and redistribution of positive and negative ions, thereby generating an ionic piezoelectric signal.
[0018] Bacterial cellulose nanofiber networks obtained directly from bacterial cultures are natural layered nanofiber networks. If indirect culture processes such as dissolution and regeneration are used to prepare bacterial cellulose hydrogels, the cellulose crystal form and nanofiber diameter within the material will change, making it impossible to form a natural layered nanofiber network structure. Natural layered nanofiber networks can induce preferential migration of ions along the in-plane direction, thus forming an in-plane dominant anisotropic ion piezoelectric output characteristic. This in-plane dominant output essentially corresponds to the d31-dominated anisotropic ion piezoelectric output characteristic—that is, when ultrasound acts along the thickness 3 direction, the generated electric field is output along the in-plane 1 direction, achieving cross-conversion between ultrasound in the thickness direction and electrical energy in the in-plane direction. This natural directionality highly matches the axial tissue structure of the corpus spongiosum, because directional electrical stimulation applied along the long axis of the tissue can guide cells to migrate and align axially through electrotactic mechanisms. Therefore, ion piezoelectric hydrogels with bacterial cellulose nanofiber networks obtained directly from bacterial cultures as the structural network can be used for the repair of corpus spongiosum defects.
[0019] The ion-piezoelectric hydrogel of the present invention can be used for the repair of defects in the corpus spongiosum of the urethra by using ultrasound as a non-contact driving method. This can achieve continuous mechanical stimulation of deep tissues, so that the implanted material can continuously generate stable ion-piezoelectric signals in the body, forming a biomimetic bioelectric microenvironment that is closer to the ion-electric activity of natural tissues.
[0020] The ion-piezoelectric hydrogel of this invention can generate ion-piezoelectric signals through a natural layered nanofiber network and ion migration regulated by fixed charge under ultrasonic irradiation, thereby simulating the bioelectric microenvironment in the corpus spongiosum tissue. This invention achieves piezoelectric response based on ion migration mechanisms. Compared to traditional piezoelectric materials that rely on electronic polarization mechanisms, its ion-piezoelectric behavior is closer to the ion conduction and bioelectric signal generation mechanisms in natural biological tissues, making it particularly suitable for tissue repair in water-rich and ion-rich physiological environments.
[0021] As a preferred technical solution: The ion-piezoelectric hydrogel for repairing corpus spongiosum defects, as described above, has bacterial cellulose nanofibers with a diameter of 22-85 nm and a water content of 84.8 wt%-93.2 wt%.
[0022] The ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum as described above uses a sodium chloride solution, potassium chloride solution, or calcium chloride solution as the salt solution, with a concentration of 0.1~1M.
[0023] The ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum as described above uses a sodium chloride solution with a concentration of 0.15M.
[0024] This invention discovers a synergistic relationship between ion piezoelectric properties and physiological saline environment. The optimal ion migration state can be achieved by adjusting the concentration of the saline solution. In particular, the optimal ion piezoelectric output can be obtained by using a 0.15M sodium chloride solution, which makes the material have a more stable electrical stimulation ability in the physiological environment.
[0025] The ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, as described above, has bacterial cellulose nanofibers that are mechanically stretched and oriented to form an oriented arrangement structure with the orientation direction consistent with the in-plane 1 direction, and the Hermans orientation factor is 0.40~0.80.
[0026] This invention uses mechanical stretching and directional training to orient bacterial cellulose nanofibers along a predetermined direction. On the one hand, it can construct continuous low-resistivity ion migration channels, allowing ions to migrate preferentially along the in-plane direction, thereby further improving the electromechanical conversion efficiency and ion piezoelectric output capability. On the other hand, it is beneficial to promote the directional migration and orderly reconstruction of blood vessels and smooth muscle along the tissue axis. In addition, it can also improve the mechanical properties of the material along the orientation direction.
[0027] As described above, an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum has bacterial cellulose nanofibers with fixed charge groups introduced through chemical modification. The fixed charge groups are used to restrict the movement of one of the positive and negative ions. The distribution density of the fixed charge groups in the bacterial cellulose nanofibers is 0.13~1.15 mmol / g (when calculating the distribution density, the mass in the denominator is the mass of the oven-dry bacterial cellulose nanofibers).
[0028] This invention introduces fixed-charge groups into bacterial cellulose nanofibers through chemical modification, enhancing the internal electric double-layer structure and asymmetric ion migration capabilities, thereby significantly improving the ion piezoelectric output characteristics. In a salt ion environment, the fixed-charge groups and migratable ions form a dynamic ion distribution structure. When the hydrogel is subjected to ultrasonic stimulation or mechanical deformation, it can induce asymmetric migration and redistribution of ions, thereby generating an ion piezoelectric signal. By synergistically regulating the fixed charge density, orientation degree, and salt ion concentration, the ion piezoelectric output performance can be effectively adjusted.
[0029] This invention also provides a method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum as described above, comprising the following steps: (a) Chemically modifying bacterial cellulose hydrogels to introduce fixed charge groups; (b) The water in the chemically modified bacterial cellulose hydrogel is replaced with an organic solvent (e.g., one or more of N-methylpyrrolidone, propylene glycol or ethylene glycol) to obtain a bacterial cellulose organic gel; The purpose of solvent displacement is to break the hydrogen bonds between fibers, which is beneficial for the next step of stretching and orientation. (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; (d) The bacterial cellulose organic gel after mechanical stretching and orientation training was soaked in water for 3-5 days to replace the organic solvent with water, thus obtaining the modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution for ion equilibration treatment to obtain an ion-piezoelectric hydrogel for the repair of urethral sponge defects.
[0030] Existing technologies for directional stretching of hydrogels often require post-crosslinking treatment to fix the orientation structure. This invention does not require post-crosslinking treatment because during mechanical stretching, the originally partially disordered nanofiber bundles are reoriented along the stretching direction, and the interfiber hydrogen bond network is reconstructed, thereby forming a stable anisotropic oriented fiber structure. Since this structure is essentially a rearrangement of the nanofiber skeleton rather than a simple change in polymer chain conformation, it is not prone to significant shrinkage after the external force is removed.
[0031] Furthermore, this invention employs orientation training after organic solvent replacement. The organic solvent reduces hydration between fibers, promotes the proximity and rearrangement of nanofibers, and improves the contact stability between fiber bundles, making the orientation structure formed by stretching easier to "lock in." Subsequently, after rehydration treatment, the original highly crystalline hydrogen bond network of bacterial cellulose is re-stabilized, thereby further fixing the orientation structure. Therefore, a high degree of orientation can be maintained for a long time without additional post-crosslinking.
[0032] As a preferred technical solution: As described above, in step (a), the bacterial cellulose hydrogel is chemically modified, that is, the bacterial cellulose hydrogel is oxidized or quaternized. Oxidative modification is performed using a 2,2,6,6-tetramethylpiperidine oxide / sodium hypochlorite oxidation system, or first using a 2,2,6,6-tetramethylpiperidine oxide / sodium hypochlorite oxidation system, followed by a sodium chlorite oxidation system. The process of oxidative modification of bacterial cellulose hydrogel using the 2,2,6,6-tetramethylpiperidine oxide / sodium hypochlorite system is as follows: First, 0.016~0.032g of 2,2,6,6-tetramethylpiperidine oxide and 0.1~0.2g of sodium bromide are added to 20~40mL of water (distilled water), and then poured into the bacterial cellulose hydrogel (dry weight 1g, water content 99wt%). Then, 0.47~2.84g of sodium hypochlorite solution (available chlorine 7.5wt%) is added to initiate the reaction. The pH of the system is maintained at around 10.5, and the reaction is carried out for 1~2 hours. After the reaction is completed, the pH of the system is adjusted to neutral, and then the system is soaked and washed. The process of oxidative modification of bacterial cellulose hydrogel using sodium hypochlorite oxidation system is as follows: 1 g of bacterial cellulose hydrogel (dry weight) oxidized by 2,2,6,6-tetramethylpiperidine oxide / sodium hypochlorite system is placed in 200-400 mL of sodium hypochlorite aqueous solution with pH 4-5, and stirred in the dark for 24-48 h. After the reaction is completed, the hydrogel is soaked and washed. Quaternization modification was performed using 3-chloro-2-hydroxypropyltrimethylammonium chloride; The quaternization modification process is as follows: bacterial cellulose hydrogel (dry weight 1g, water content 99wt%) is soaked in 200~400mL of sodium hydroxide aqueous solution with a concentration of 1~2wt%, and then 3-chloro-2-hydroxypropyltrimethylammonium chloride (4~8g of 3-chloro-2-hydroxypropyltrimethylammonium chloride is added dropwise) is added. The mixture is then reacted at 60~65℃ for 10~12h. After the reaction is completed, the mixture is soaked and washed.
[0033] As described above, in step (c), the mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a tensile rate of 10 mm / min, with a tensile strain of 20% to 40%, and the tensile state is maintained for 12 to 24 hours for shaping.
[0034] In the method described above, the soaking time in step (e) is 12-24 hours.
[0035] Beneficial effects
[0036] (1) The present invention constructs an ion piezoelectric hydrogel using a bacterial cellulose nanofiber network as the structural network. It can generate ion piezoelectric signals under ultrasonic stimulation, and achieve wireless bioelectric stimulation without the need for an external power source. This solves the problem that existing repair materials lack active bioelectric stimulation capabilities and are difficult to simulate the bioelectric microenvironment of natural tissues.
[0037] (2) The ion piezoelectric hydrogel prepared by the present invention has anisotropic ion piezoelectric output characteristics. The ion piezoelectric output in d31 mode is higher than that in d33 mode, which can match the axial tissue structure of the corpus spongiosum of the urethra and solve the problem that the existing ion piezoelectric hydrogel has weak ion migration directionality and cannot provide effective directional electrical stimulation.
[0038] (3) After the ion piezoelectric hydrogel prepared by the present invention is implanted into the defect site of the corpus spongiosum, it can promote angiogenesis, smooth muscle reconstruction and corpus spongiosum tissue repair, realize the functional reconstruction of corpus spongiosum tissue, and solve the problem that existing materials are difficult to promote the functional repair of corpus spongiosum. Attached Figure Description
[0039] Figure 1 This is a physical image of the ion piezoelectric output voltage testing system; Figure 2 The d31 mode ion piezoelectric output voltage curve of the ion piezoelectric hydrogel used for repairing corpus spongiosum defects in Example 1; Figure 3 The d33 mode ion piezoelectric output voltage curve of the ion piezoelectric hydrogel used for repairing corpus spongiosum defects in Example 1; Figure 4 This is a SEM image of the surface of the ion-piezoelectric hydrogel used for repairing defects of the corpus spongiosum in Example 5. Figure 5 The d31 mode ion piezoelectric output voltage curve of the ion piezoelectric hydrogel for repairing urethral sponge defects in Embodiment 6 of the present invention; Figure 6 The d33 mode ion piezoelectric output voltage curve of the ion piezoelectric hydrogel used for repairing corpus spongiosum defects in Example 6; Figure 7SEM image of the surface of the ion-piezoelectric hydrogel used for repairing corpus spongiosum defects in Example 9; Figure 8 The salt concentration-d31 mode ion piezoelectric output voltage variation curves of the ion piezoelectric hydrogels used for urethral sponge defect repair in Examples 9-12 are shown. Detailed Implementation
[0040] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0041] The following are the test methods for the relevant performance indicators in each embodiment: Moisture content: Determined by gravimetric method. After gently blotting off surface free water with filter paper, the wet weight of the sample was immediately measured. The sample was then freeze-dried in a freeze dryer for 48 hours until constant weight, and the dry weight was measured. The moisture content of the ion-piezoelectric hydrogel was calculated according to the following formula: W c =(W w -W d )×100% / W w ; In the formula, W c W represents the moisture content (%). w W represents the wet weight (g) of the sample after surface free water has been removed. d The dry weight (g) of the sample after freeze-drying to constant weight. Each group of samples was measured in parallel three times, and the average value was taken.
[0042] Hermans orientation factor: determined using a two-dimensional wide-angle X-ray diffractometer (2D-WAXD). The samples were freeze-dried and cut into 10mm × 10mm pieces, and tested at room temperature. Cu Kα rays (characteristic X-ray wavelength λ = 0.15418 nm), a working voltage of 40 kV, and a working current of 40 mA were used. The azimuth angle of the (200) crystal plane (2θ = 22.0~22.5°) of cellulose type I crystals was selected. φ Integrating to obtain the azimuth intensity distribution curve I ( φ ); Calculate the Hermans orientation factor S according to the following formula: ; ; .
[0043] Distribution density of fixed charge groups in oxidized bacterial cellulose nanofibers: The oxidized bacterial cellulose material was freeze-dried to obtain oven-dried oxidized bacterial cellulose nanofibers; 0.2 g of oven-dried oxidized bacterial cellulose nanofibers were weighed and placed in 100 mL of 0.01 mol / L NaCl aqueous solution, and homogenized using a high-speed homogenizer (8000 rpm, 20 min) to prepare a nanocellulose dispersion with water as the dispersion medium; 0.1 mol / L HCl aqueous solution was added to the dispersion to adjust the pH of the system to 2.5~3.0, and then conductivity titration was performed using 0.05 mol / L NaOH aqueous solution; the amount of NaOH aqueous solution consumed and the corresponding conductivity were recorded in real time during the titration process, and a titration curve was plotted. The volumes of the first equivalence point V1 and the second equivalence point V2 were determined by two-segment linear fitting; the carboxyl content was calculated according to the formula C... a (V2−V1)×1000 / m a Calculate the fixed charge group distribution density, where C a V1 is the concentration of NaOH aqueous solution (mol / L), V2 is the volume of NaOH aqueous solution consumed at the first equivalence point (L), and m is the volume of NaOH aqueous solution consumed at the second equivalence point (L). a The mass (g) of the oven-dried oxidizing bacterial cellulose nanofibers.
[0044] Distribution density of fixed charge groups in quaternized ammonium-modified bacterial cellulose nanofibers: After quaternization modification, the bacterial cellulose material (before organic solvent replacement and salt solution ion equilibrium treatment) was continuously washed with deionized water for at least 72 hours (water changed every 12 hours), freeze-dried for 48 hours, and then vacuum-dried at 60℃ to constant weight to obtain oven-dried quaternized ammonium-modified bacterial cellulose nanofibers. The nitrogen mass fraction of the oven-dried quaternized ammonium-modified bacterial cellulose nanofibers was determined using a CHNS mode organic elemental analyzer. Simultaneously, the background nitrogen content of untreated bacterial cellulose was determined and subtracted. The content of quaternary ammonium salt groups was calculated using the formula: quaternary ammonium salt group content = 0.7139 (N...). QBC -N BC Calculate the fixed charge group distribution density, where N QBC The nitrogen mass fraction (wt%) of quaternized bacterial cellulose, N BC The nitrogen mass fraction (wt%) of unquaternized bacterial cellulose is expressed as a percentage. Each quaternary ammonium salt group contains one nitrogen atom, and the measured net nitrogen molar amount is the molar amount of the quaternary ammonium group.
[0045] Ion piezoelectric output voltage: Utilizes an ultrasonic stimulation-oscilloscope combined system (see actual product). Figure 1The system, consisting of a medical ultrasound therapy device (model UT1021, Nu-Tek) and a digital oscilloscope (model MSO5034HD, Uni-Tek), was used for testing. Before testing, the ion-piezoelectric hydrogel was cut into rectangular samples measuring 30mm in length, 20mm in width, and 3mm in thickness, and equilibrated for 30 minutes in an environment with a temperature of 25±1℃ and a relative humidity of 50±5%. In d31 mode testing, two 0.2mm diameter platinum wire electrodes were inserted parallel to each other along the in-plane stretching direction (1-axis direction) at both ends of the sample, with a 10mm electrode spacing. In d33 mode testing, two 0.2mm diameter platinum wire electrodes were inserted... Platinum wire electrodes of m were attached to the upper and lower surfaces of the sample (3-axis direction) for signal acquisition. The electrodes were connected to the oscilloscope input terminal, and the electrode connection points were sealed with transparent insulating tape to prevent detachment and external electromagnetic interference during testing. During testing, the sample was fixed on a polylactic acid fixing plate and secured around the perimeter with clamps to prevent displacement. The ultrasonic probe was in contact with the upper surface of the sample through a medical ultrasonic coupling agent, with the probe center perpendicular to the sample thickness direction (3-axis direction), maintaining stable contact between the probe and the sample surface. The ultrasonic stimulation conditions were set as follows: frequency 1MHz, power density 0.1~2.0W / cm². 2 The test was conducted in pulse mode with a 50% duty cycle. Each stimulus lasted 5 seconds, followed by a 60-second pause, for a total of 5 cycles. During the test, a digital oscilloscope was used to acquire the open-circuit voltage signal in real time, with a sampling frequency of 500MHz. Data analysis was performed by recording three consecutive stable stimulus cycles. For each stable stimulation cycle, the moment the ultrasound was turned on was recorded as 0s, and the period from 0 to 5s during ultrasound stimulation was used as the data analysis time window. For each data analysis time window, all positive voltage sampling points and all negative voltage sampling points within that time window were extracted. For each data analysis time window, all instantaneous open-circuit voltage sampling values greater than 0 and all instantaneous open-circuit voltage sampling values less than 0 were extracted. The arithmetic mean of the positive voltage sampling values and the arithmetic mean of the negative voltage sampling values were calculated. The difference between the positive voltage average value and the negative voltage average value was used as the ion piezoelectric output voltage of that stimulation cycle. The arithmetic mean of the ion piezoelectric output voltages obtained from three consecutive stable stimulation cycles was taken as the ion piezoelectric output voltage of that sample. At least three independent samples were tested in each group, and the arithmetic mean of the ion piezoelectric output voltages of each sample was taken as the final result, in mV.
[0046] The proportion of mature blood vessel area and smooth muscle area were evaluated through animal experiments combined with histological and immunohistochemical staining. New Zealand white rabbits weighing 2.5–3.0 kg were selected to establish a rabbit corpus spongiosum defect model. Under aseptic conditions, a tissue defect area of 10 mm long, 5 mm wide, and 3 mm deep was formed in the corpus spongiosum. An ion-piezoelectric hydrogel scaffold was implanted into the defect site and then sutured in place. After implantation, in vitro percutaneous ultrasound stimulation was used to induce continuous generation of ion-piezoelectric signals in vivo from the ion-piezoelectric hydrogel. Ultrasound stimulation was performed using a medical ultrasound therapy device (model UT1021, Nu-Tek). The probe was in contact with the perineal skin of the animal through a medical ultrasound coupling agent, with the center of the probe perpendicularly aligned with the implantation area. The stimulation parameters were set as follows: frequency 1.0 MHz, power density 1 W / cm². 2 The experiment was conducted using a 50% duty cycle and pulsed mode; each stimulation lasted 5 minutes, once daily, for 6 consecutive days per week, for 12 weeks. Three months post-surgery, the rabbits were sacrificed, and the reconstructed urethral tissue was fixed in 10% formalin, dehydrated, embedded in paraffin, and then prepared into tissue sections. Hematoxylin-eosin (H&E), Masson staining, and immunohistochemical staining were performed. Immunohistochemical staining used CD31 (platelet endothelial cell adhesion molecule) as a vascular endothelial marker and α-SMA (α-smooth muscle actin) as a marker for vascular smooth muscle and smooth muscle tissue. Five fields of view were randomly selected under an optical microscope (Olympus BX53) for image capture, and ImageJ software was used for quantitative image analysis: the percentage of mature blood vessel area was defined as the area of CD31 and α-SMA double-positive regions relative to the total tissue cross-sectional area; the percentage of smooth muscle area was defined as the percentage of α-SMA positive regions relative to the total tissue cross-sectional area. At least three samples were tested in each group, and the average value was used as the final result.
[0047] Example 1
[0048] A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, the specific steps of which are as follows: (1) Preparation of main materials; 2,2,6,6-Tetramethylpiperidine oxide; Sodium bromide; water; Bacterial cellulose hydrogel: Manufacturer: Hainan Guangyu Biotechnology Co., Ltd., code: M-1, dimensions: 32cm×24cm×0.3cm, water content: 99wt%; Sodium hypochlorite solution: Manufacturer: Shanghai Maclean Biochemical Technology Co., Ltd., Product No.: S817441, Available chlorine: 7.5 wt%; Organic solvent: N-methylpyrrolidone; Salt solution: Sodium chloride aqueous solution, concentration 1M; (2) Preparation of ion-piezoelectric hydrogels for the repair of corpus spongiosum defects; (a) Chemical modification of bacterial cellulose hydrogels; First, 0.016 g of 2,2,6,6-tetramethylpiperidine oxide and 0.1 g of sodium bromide were added to 20 mL of water and then poured into bacterial cellulose hydrogel (dry weight 1 g). Then, 0.47 g of sodium hypochlorite solution was added to initiate the reaction. The pH of the system was maintained at 10.5 and the reaction was carried out for 1 h. After the reaction was completed, the pH of the system was adjusted to neutral and then soaked and washed. (b) The water in the chemically modified bacterial cellulose hydrogel was replaced with an organic solvent to obtain a bacterial cellulose organic gel; (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; The mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a stretching rate of 10 mm / min, with a tensile strain of 20%, and the stretching state is maintained for 12 hours for shaping. (d) The bacterial cellulose organic gel after mechanical stretching and orientation training was soaked in water for 3 days to replace the organic solvent in it with water, thus obtaining modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution for 12 h for ion equilibration treatment to obtain an ion-piezoelectric hydrogel for the repair of urethral sponge defects.
[0049] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects consists of a structural network and a salt solution distributed within the network. The structural network is a bacterial cellulose nanofiber network obtained directly from bacterial culture. The diameter of the bacterial cellulose nanofibers is 30-85 nm, and the water content of the ion-piezoelectric hydrogel is 93.2 wt%. The bacterial cellulose nanofibers are mechanically stretched and oriented to form an oriented structure, with the orientation direction consistent with the in-plane 1 direction, and the Hermans orientation factor is 0.40. The bacterial cellulose nanofibers have fixed charge groups introduced through chemical modification. These fixed charge groups are used to restrict the movement of one of the positive or negative ions. The distribution density of the fixed charge groups in the bacterial cellulose nanofibers is 0.13 mmol / g. Ionic piezoelectric hydrogels at an ultrasonic strength of 0.3 W / cm 2 Under ultrasonic stimulation, an ion piezoelectric output voltage of 457.1 mV can be generated, and the d31 mode ion piezoelectric output voltage is higher than that of the d33 mode ion piezoelectric output voltage. The d31 mode ion piezoelectric output voltage is 254.3 mV (the d31 mode ion piezoelectric output voltage curve is shown in Figure 1). Figure 2 As shown), the d33 mode ion piezoelectric output voltage is 202.8mV (the d33 mode ion piezoelectric output voltage curve is shown in Figure 1). Figure 3(As shown in the figure) After implantation, the ion-piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the proportion of mature blood vessels reached 6.6% and the proportion of smooth muscle reached 25.4%.
[0050] Example 2
[0051] A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, the specific steps of which are as follows: (1) Preparation of main materials; 2,2,6,6-Tetramethylpiperidine oxide; Sodium bromide; water; Bacterial cellulose hydrogel: Manufacturer: Hainan Guangyu Biotechnology Co., Ltd., code: M-1, dimensions: 32cm×24cm×0.3cm, water content: 99wt%; Sodium hypochlorite solution: Manufacturer: Shanghai Maclean Biochemical Technology Co., Ltd., Product No.: S817441, Available chlorine: 7.5 wt%; Organic solvent: propylene glycol; Salt solution: potassium chloride aqueous solution, concentration 0.3M; (2) Preparation of ion-piezoelectric hydrogels for the repair of corpus spongiosum defects; (a) Chemical modification of bacterial cellulose hydrogels; First, 0.024 g of 2,2,6,6-tetramethylpiperidine oxide and 0.15 g of sodium bromide were added to 30 mL of water and then poured into bacterial cellulose hydrogel (dry weight 1 g). Then, 1.89 g of sodium hypochlorite solution was added to initiate the reaction. The pH of the system was maintained at 10.5 and the reaction was carried out for 1.5 h. After the reaction was completed, the pH of the system was adjusted to neutral. (b) The water in the chemically modified bacterial cellulose hydrogel was replaced with an organic solvent to obtain a bacterial cellulose organic gel; (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; The mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a stretching rate of 10 mm / min, with a tensile strain of 30%, and the stretching state is maintained for 18 hours for shaping. (d) The bacterial cellulose organic gel after mechanical stretching and orientation training was soaked in water for 3 days to replace the organic solvent in it with water, thus obtaining modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution for 18 hours to perform ion equilibration treatment, and an ion-piezoelectric hydrogel for the repair of urethral sponge defects was obtained.
[0052] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects consists of a structural network and a salt solution distributed within the network. The structural network is a bacterial cellulose nanofiber network obtained directly from bacterial culture. The diameter of the bacterial cellulose nanofibers is 28-60 nm, and the water content of the ion-piezoelectric hydrogel is 88.5 wt%. The bacterial cellulose nanofibers are mechanically stretched and oriented to form an oriented structure, with the orientation direction consistent with the in-plane 1 direction, and the Hermans orientation factor is 0.50. The bacterial cellulose nanofibers have fixed charge groups introduced through chemical modification. These fixed charge groups are used to restrict the movement of one of the positive or negative ions, and the distribution density of the fixed charge groups in the bacterial cellulose nanofibers is 0.5 mmol / g. Ionic piezoelectric hydrogels at an ultrasonic strength of 0.5 W / cm 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 818.3mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 457.1mV, and that of d33 mode is 361.2mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 7.8% and the smooth muscle area accounts for 29%.
[0053] Example 3
[0054] A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, the specific steps of which are as follows: (1) Preparation of main materials; 2,2,6,6-Tetramethylpiperidine oxide; Sodium bromide; water; Bacterial cellulose hydrogel: Manufacturer: Hainan Guangyu Biotechnology Co., Ltd., code: M-1, dimensions: 32cm×24cm×0.3cm, water content: 99wt%; Sodium hypochlorite solution: Manufacturer: Shanghai Maclean Biochemical Technology Co., Ltd., Product No.: S817441, Available chlorine: 7.5 wt%; Sodium chlorite aqueous solution: composed of sodium chlorite, water and hydrochloric acid, with a sodium chlorite concentration of 0.45 wt% and a pH value of 4. Organic solvent: propylene glycol; Salt solution: 0.1M calcium chloride aqueous solution; (2) Preparation of ion-piezoelectric hydrogels for the repair of corpus spongiosum defects; (a) Chemical modification of bacterial cellulose hydrogels; First, 0.032 g of 2,2,6,6-tetramethylpiperidine oxide and 0.2 g of sodium bromide were added to 40 mL of water and then poured into bacterial cellulose hydrogel (dry weight 1 g). Then, 2.84 g of sodium hypochlorite solution was added to initiate the reaction. The pH of the system was maintained at 10.5 and the reaction was carried out for 2 h. After the reaction was completed, the pH of the system was adjusted to neutral and then soaked and washed. Finally, the system was placed in 200 mL of sodium chlorite aqueous solution and stirred in the dark for 24 h. After the reaction was completed, the system was soaked and washed. (b) The water in the chemically modified bacterial cellulose hydrogel was replaced with an organic solvent to obtain a bacterial cellulose organic gel; (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; The mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a stretching rate of 10 mm / min, with a tensile strain of 35%, and the stretching state is maintained for 18 hours for shaping. (d) The bacterial cellulose organic gel after mechanical stretching and orientation training was soaked in water for 4 days to replace the organic solvent in it with water, thus obtaining modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution for 18 hours to perform ion equilibration treatment, and an ion-piezoelectric hydrogel for the repair of urethral sponge defects was obtained.
[0055] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects consists of a structural network and a salt solution distributed within the network. The structural network is a bacterial cellulose nanofiber network obtained directly from bacterial culture. The diameter of the bacterial cellulose nanofibers is 25-55 nm, and the water content of the ion-piezoelectric hydrogel is 86.1 wt%. The bacterial cellulose nanofibers are mechanically stretched and oriented to form an oriented structure, with the orientation direction consistent with the in-plane 1 direction, and the Hermans orientation factor is 0.65. The bacterial cellulose nanofibers have fixed charge groups introduced through chemical modification. These fixed charge groups are used to restrict the movement of one of the positive or negative ions. The distribution density of the fixed charge groups in the bacterial cellulose nanofibers is 0.83 mmol / g. Ionic piezoelectric hydrogels at an ultrasonic strength of 0.8 W / cm 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 1241.9mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 756.3mV, and that of d33 mode is 485.6mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 8.9% and the smooth muscle area accounts for 33.1%.
[0056] Example 4 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, the specific steps of which are as follows: (1) Preparation of main materials; Bacterial cellulose hydrogel: Manufacturer: Hainan Guangyu Biotechnology Co., Ltd., code: M-1, dimensions: 32cm×24cm×0.3cm, water content: 99wt%; Sodium hydroxide aqueous solution: concentration 2 wt% 3-Chloro-2-hydroxypropyltrimethylammonium chloride; Organic solvent: ethylene glycol; Salt solution: 0.1M aqueous solution of sodium chloride; water; (2) Preparation of ion-piezoelectric hydrogels for the repair of corpus spongiosum defects; (a) Chemical modification of bacterial cellulose hydrogels; After soaking bacterial cellulose hydrogel (dry weight 1g) in 400mL of sodium hydroxide aqueous solution, 3-chloro-2-hydroxypropyltrimethylammonium chloride (8g in total) was added dropwise and reacted at 65℃ for 12h. After the reaction was completed, the sample was soaked and washed. (b) The water in the chemically modified bacterial cellulose hydrogel was replaced with an organic solvent to obtain a bacterial cellulose organic gel; (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; The mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a stretching rate of 10 mm / min, with a tensile strain of 38%, and the tensile state is maintained for 24 hours for shaping. (d) The bacterial cellulose organic gel after mechanical stretching and orientation training was soaked in water for 4 days to replace the organic solvent in it with water, thus obtaining modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution for 12 h for ion equilibration treatment to obtain an ion-piezoelectric hydrogel for the repair of urethral sponge defects.
[0057] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects consists of a structural network and a salt solution distributed within the network. The structural network is a bacterial cellulose nanofiber network obtained directly from bacterial culture. The diameter of the bacterial cellulose nanofibers is 35-70 nm, and the water content of the ion-piezoelectric hydrogel is 88.8 wt%. The bacterial cellulose nanofibers are mechanically stretched and oriented to form an oriented structure, with the orientation direction consistent with the in-plane 1 direction, and the Hermans orientation factor is 0.76. The bacterial cellulose nanofibers have fixed charge groups introduced through chemical modification. These fixed charge groups are used to restrict the movement of one of the positive or negative ions. The distribution density of the fixed charge groups in the bacterial cellulose nanofibers is 1.05 mmol / g. Ionic piezoelectric hydrogels at an ultrasonic strength of 2.0 W / cm 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 766.2mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 468.4mV, and that of d33 mode is 297.8mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 7.5% and the smooth muscle area accounts for 28%.
[0058] Example 5 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, the specific steps of which are as follows: (1) Preparation of main materials; Bacterial cellulose hydrogel: Manufacturer: Hainan Guangyu Biotechnology Co., Ltd., code: M-1, dimensions: 32cm×24cm×0.3cm, water content: 99wt%; Sodium hydroxide aqueous solution: concentration 1 wt% 3-Chloro-2-hydroxypropyltrimethylammonium chloride; Organic solvent: ethylene glycol; Salt solution: 0.5M aqueous solution of sodium chloride; water; (2) Preparation of ion-piezoelectric hydrogels for the repair of corpus spongiosum defects; (a) Chemical modification of bacterial cellulose hydrogels; After soaking bacterial cellulose hydrogel (dry weight 1g) in 200mL of sodium hydroxide aqueous solution, 3-chloro-2-hydroxypropyltrimethylammonium chloride (4g in total) was added dropwise and reacted at 60℃ for 10h. After the reaction was completed, the sample was soaked and washed. (b) The water in the chemically modified bacterial cellulose hydrogel was replaced with an organic solvent to obtain a bacterial cellulose organic gel; (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; The mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a stretching rate of 10 mm / min, with a tensile strain of 20%, and the stretching state is maintained for 24 hours for shaping. (d) The bacterial cellulose organic gel after mechanical stretching and orientation training was soaked in water for 5 days to replace the organic solvent with water, thus obtaining modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution for 24 hours to perform ion equilibration treatment, and an ion-piezoelectric hydrogel for the repair of urethral sponge defects was obtained.
[0059] The final ion-piezoelectric hydrogel used for the repair of corpus spongiosum defects (SEM images of the surface are shown in [image missing]). Figure 4 The study consists of a structural network and a salt solution distributed within the network. The structural network is a bacterial cellulose nanofiber network obtained directly from bacterial culture. The diameter of the bacterial cellulose nanofibers is 35-75 nm, and the water content of the ion-piezoelectric hydrogel is 91.5 wt%. The bacterial cellulose nanofibers are mechanically stretched and oriented to form an oriented structure, with the orientation direction consistent with the in-plane 1 direction, and the Hermans orientation factor is 0.40. The bacterial cellulose nanofibers have fixed charge groups introduced through chemical modification. The fixed charge groups are used to restrict the movement of one of the positive and negative ions. The distribution density of the fixed charge groups in the bacterial cellulose nanofibers is 0.8 mmol / g. Ionic piezoelectric hydrogels at an ultrasonic strength of 1 W / cm 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 692.9mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 405.3mV, and that of d33 mode is 287.6mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and repair of corpus spongiosum tissue. Three months after implantation, the proportion of mature blood vessel area reached 7.2%, and the proportion of smooth muscle area reached 27.6%.
[0060] Example 6 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, the specific steps of which are as follows: (1) Preparation of main materials; 2,2,6,6-Tetramethylpiperidine oxide; Sodium bromide; water; Bacterial cellulose hydrogel: Manufacturer: Hainan Guangyu Biotechnology Co., Ltd., code: M-1, dimensions: 32cm×24cm×0.3cm, water content: 99wt%; Sodium hypochlorite solution: Manufacturer: Shanghai Maclean Biochemical Technology Co., Ltd., Product No.: S817441, Available chlorine: 7.5 wt%; Sodium chlorite aqueous solution: composed of sodium chlorite, water and hydrochloric acid, with a sodium chlorite concentration of 0.45 wt% and a pH value of 5; Organic solvent: N-methylpyrrolidone; Salt solution: Sodium chloride aqueous solution, concentration 0.15M; (2) Preparation of ion-piezoelectric hydrogels for the repair of corpus spongiosum defects; (a) Chemical modification of bacterial cellulose hydrogels; First, 0.032 g of 2,2,6,6-tetramethylpiperidine oxide and 0.2 g of sodium bromide were added to 40 mL of water and then poured into bacterial cellulose hydrogel (dry weight 1 g). Then, 2.84 g of sodium hypochlorite solution was added to initiate the reaction. The pH of the system was maintained at 10.5 and the reaction was carried out for 1 h. After the reaction was completed, the pH of the system was adjusted to neutral, and then the system was soaked and washed. Finally, the system was placed in 400 mL of sodium chlorite aqueous solution and stirred in the dark for 48 h. After the reaction was completed, the system was soaked and washed. (b) The water in the chemically modified bacterial cellulose hydrogel was replaced with an organic solvent to obtain a bacterial cellulose organic gel; (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; The mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a stretching rate of 10 mm / min, with a tensile strain of 40%, and the stretching state is maintained for 24 hours for shaping. (d) The bacterial cellulose organic gel after mechanical stretching and orientation training was soaked in water for 5 days to replace the organic solvent with water, thus obtaining modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution for 24 hours to perform ion equilibration treatment, and an ion-piezoelectric hydrogel for the repair of urethral sponge defects was obtained.
[0061] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects consists of a structural network and a salt solution distributed within the network. The structural network is a bacterial cellulose nanofiber network obtained directly from bacterial culture. The diameter of the bacterial cellulose nanofibers is 22-50 nm, and the water content of the ion-piezoelectric hydrogel is 84.8 wt%. The bacterial cellulose nanofibers are mechanically stretched and oriented to form an oriented structure, with the orientation direction consistent with the in-plane 1 direction, and the Hermans orientation factor is 0.80. The bacterial cellulose nanofibers have fixed charge groups introduced through chemical modification. These fixed charge groups are used to restrict the movement of one of the positive or negative ions. The distribution density of the fixed charge groups in the bacterial cellulose nanofibers is 1.15 mmol / g. Ionic piezoelectric hydrogels at an ultrasonic strength of 1 W / cm 2 Under ultrasonic stimulation, it can generate an ion piezoelectric output voltage of 1944.7mV, and the d31 mode ion piezoelectric output voltage is higher than that of the d33 mode ion piezoelectric output voltage. The d31 mode ion piezoelectric output voltage is 1080.5mV (the d31 mode ion piezoelectric output voltage curve is shown in Figure 1). Figure 5 As shown), the d33 mode ion piezoelectric output voltage is 864.2mV (the d33 mode ion piezoelectric output voltage curve is shown in Figure 1). Figure 6 (As shown in the figure) After implantation, the ion-piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 9.8% and the smooth muscle area accounts for 38%.
[0062] Example 7 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum is different from that in Example 6 except that step (a) is omitted.
[0063] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects was prepared with an ultrasonic strength of 1 W / cm. 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 1212.4mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 682.6mV, and that of d33 mode is 529.8mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 8.6% and the smooth muscle area accounts for 32%.
[0064] Compared to Example 6, Example 7 showed a decrease in ion piezoelectric output voltage, the proportion of mature blood vessel area, and the proportion of smooth muscle area. This is because without chemical modification, the number of fixed charge groups on the surface of bacterial cellulose was significantly reduced, the internal electric double layer structure of the material was weakened, and the asymmetric migration ability of ions under ultrasonic stimulation decreased, thereby weakening the ion piezoelectric effect and consequently reducing the tissue repair effect.
[0065] Example 8 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum is different from that in Example 6 except that step (c) is omitted.
[0066] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects was prepared with an ultrasonic strength of 1 W / cm. 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 1419.8mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 857.8mV, and that of d33 mode is 562mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 9.0% and the smooth muscle area accounts for 34%.
[0067] Compared with Example 6, Example 8 showed a decrease in ion piezoelectric output voltage, the proportion of mature blood vessel area, and the proportion of smooth muscle area. This is because without mechanical stretching and orientation training, the bacterial cellulose nanofibers did not form an oriented arrangement structure, increasing the resistance to in-plane ion migration, reducing the effective ion migration efficiency, and weakening both the mechanoelectric conversion efficiency and ion piezoelectric output capability, thereby diminishing the ion piezoelectric effect and tissue repair effect.
[0068] Example 9 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum is different from that of Example 6 only in that steps (a) and (c) are omitted.
[0069] The final ion-piezoelectric hydrogel used for repairing corpus spongiosum defects (SEM images of the surface are shown in [image missing]). Figure 7 At an ultrasonic intensity of 1 W / cm 2Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 911.8mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 536.5mV, and that of d33 mode is 375.3mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 7.9% and the smooth muscle area accounts for 30%.
[0070] Compared with Example 6, Example 9 showed a decrease in ion piezoelectric output voltage, the proportion of mature blood vessel area, and the proportion of smooth muscle area. This is because without chemical modification and mechanical stretching and directional training, bacterial cellulose lacked both sufficient fixed charge groups to enhance ion selective migration ability and mechanical stretching to further form directional ion migration channels to improve in-plane ion migration efficiency. Both factors combined led to a weakening of the ion piezoelectric effect and a corresponding reduction in tissue repair efficacy.
[0071] Example 10 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum is different from that in Example 9 only in that the concentration of the salt solution (sodium chloride aqueous solution) is 0.5M.
[0072] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects was prepared with an ultrasonic strength of 1 W / cm. 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 461.5mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 280mV, and that of d33 mode is 181.5mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the mature blood vessel area accounts for 6.8% and the smooth muscle area accounts for 26.2%.
[0073] Example 11 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum is different from that in Example 9 only in that the concentration of the salt solution is 1M.
[0074] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects was prepared with an ultrasonic strength of 1 W / cm. 2Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 379.6mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 203mV, and that of d33 mode is 176.6mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the proportion of mature blood vessel area reached 6.4%, and the proportion of smooth muscle area reached 24.8%.
[0075] Example 12 A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum is different from that in Example 9 only in that the concentration of the salt solution is 0.1M.
[0076] The final ion-piezoelectric hydrogel for repairing corpus spongiosum defects was prepared with an ultrasonic strength of 1 W / cm. 2 Under ultrasound stimulation, it can generate an ion piezoelectric output voltage of 611.3mV, and the ion piezoelectric output voltage of d31 mode is higher than that of d33 mode. The ion piezoelectric output voltage of d31 mode is 371.3mV, and that of d33 mode is 240mV. After implantation, the ion piezoelectric hydrogel can promote angiogenesis, smooth muscle reconstruction and urethral sponge tissue repair. Three months after implantation, the proportion of mature blood vessel area reached 7.1%, and the proportion of smooth muscle area reached 27.2%.
[0077] Compared to Example 9, in Examples 10-12, when the salt solution concentration was higher than 0.15 M, the d31 pattern (corresponding trend as shown) Figure 8 As shown in the figure, the maximum peak open-circuit voltage of the d33 mode gradually decreases with increasing salt concentration. The proportion of mature blood vessel area and smooth muscle area also decreases synchronously after 3 months of implantation. Excessively high salt concentrations enhance ion shielding, compress the fiber surface double layer, and weaken the selective regulation ability of fixed surface charges on migratable ions, hindering effective asymmetric ion migration. When the salt solution concentration is below 0.15M, the aforementioned ion piezoelectric output indicators and tissue repair indicators also decrease, because the number of migratable ions is insufficient, limiting charge separation and ion piezoelectric output under ultrasound stimulation. It can be seen that using a 0.15M salt solution yields the optimal ion piezoelectric output, enabling the material to have more stable electrical stimulation capabilities in a physiological environment.
Claims
1. An ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum, comprising a structural network and a salt solution distributed within the structural network, characterized in that, The structural network is a bacterial cellulose nanofiber network obtained by direct culture of bacterial strains.
2. The ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum according to claim 1, characterized in that, The bacterial cellulose nanofibers have a diameter of 22~85nm, and the water content of the ion-piezoelectric hydrogel is 84.8wt%~93.2wt%.
3. The ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum according to claim 1, characterized in that, The salt solution is a sodium chloride solution, potassium chloride solution, or calcium chloride solution, and the concentration of the salt solution is 0.1~1M.
4. The ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum according to claim 3, characterized in that, The salt solution is a sodium chloride solution with a concentration of 0.15M.
5. An ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum according to any one of claims 1 to 4, characterized in that, Bacterial cellulose nanofibers are mechanically stretched and oriented to form an oriented structure with the orientation direction consistent with the in-plane 1 direction. The Hermans orientation factor is 0.40~0.
80.
6. The ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum according to claim 5, characterized in that, Bacterial cellulose nanofibers have fixed charge groups introduced through chemical modification. These fixed charge groups are used to restrict the movement of one of the positive or negative ions. The distribution density of the fixed charge groups in bacterial cellulose nanofibers is 0.13~1.15 mmol / g.
7. A method for preparing an ion-piezoelectric hydrogel for repairing defects of the corpus spongiosum as described in claim 6, characterized in that, Includes the following steps: (a) Chemically modifying bacterial cellulose hydrogels to introduce fixed charge groups; (b) The water in the chemically modified bacterial cellulose hydrogel was replaced with an organic solvent to obtain a bacterial cellulose organic gel; (c) Mechanical stretching and orientation training of bacterial cellulose organic gel; (d) The organic solvent in the bacterial cellulose organic gel after mechanical stretching and orientation training was replaced with water to obtain a modified stretching bacterial cellulose hydrogel. (e) The modified stretched bacterial cellulose hydrogel was soaked in a salt solution to obtain an ion-piezoelectric hydrogel for the repair of urethral sponge defects.
8. The method according to claim 7, characterized in that, In step (a), the bacterial cellulose hydrogel is chemically modified, that is, the bacterial cellulose hydrogel is oxidized or quaternized. Oxidative modification is performed using a 2,2,6,6-tetramethylpiperidine oxide / sodium hypochlorite oxidation system, or first using a 2,2,6,6-tetramethylpiperidine oxide / sodium hypochlorite oxidation system, followed by a sodium chlorite oxidation system. The quaternization modification uses 3-chloro-2-hydroxypropyltrimethylammonium chloride.
9. The method according to claim 7, characterized in that, In step (c), the mechanical tensile orientation training process is as follows: wet stretching is performed using a universal testing machine at a stretching rate of 10 mm / min, with a tensile strain of 20%~40%, and the stretching state is maintained for 12~24 hours for shaping.
10. The method according to claim 7, characterized in that, In step (e), the soaking time is 12 to 24 hours.
Citation Information
Patent Citations
PAM ion piezoelectric hydrogel as well as preparation method and application thereof
CN120248226A
A method for preparing an ionic piezoelectric hydrogel for treatment of peripheral nerve injury
CN120586153B
